2015
DOI: 10.1002/biot.201500081
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced hydrolysis of lignocellulosic biomass: Bi‐functional enzyme complexes expressed in Pichia pastoris improve bioethanol production from Miscanthus sinensis

Abstract: Research Article Fatty acid hydration activity of a recombinant Escherichia coli-based biocatalyst is improved through targeting the oleate hydratase into the periplasm Sang

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 28 publications
0
7
0
1
Order By: Relevance
“…Additionally, chimeric enzymes with dockerin domains have also been used to assemble complexes via cohesin‐dockerin interactions . Previous reports have described the use of this interaction between dockerin and cohesin for the construction of protein complexes composed of endoglucanase or xylanase with increased hydrolytic ability with cellulose or hemicellulose as substrates, respectively .…”
Section: Protein Scaffolds For Biomass Conversion and Immobilizationmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, chimeric enzymes with dockerin domains have also been used to assemble complexes via cohesin‐dockerin interactions . Previous reports have described the use of this interaction between dockerin and cohesin for the construction of protein complexes composed of endoglucanase or xylanase with increased hydrolytic ability with cellulose or hemicellulose as substrates, respectively .…”
Section: Protein Scaffolds For Biomass Conversion and Immobilizationmentioning
confidence: 99%
“…Previous reports have demonstrated that enzyme complexes enabled the effective targeting and concentration of the hydrolytic action through enzyme proximity effect by a coordinated organization . Additionally, these minicellulosomes could be recycled by single‐step CBM‐based recycling methods .…”
Section: Protein Scaffolds For Biomass Conversion and Immobilizationmentioning
confidence: 99%
See 2 more Smart Citations
“…ZHA et al (2013) identificaram uma cepa de Pichia anomala como capaz de assimilar pentoses e promissora para produção de bioetanol a partir de material celulósico. A levedura Pichia pastoris é muito estudada por seu potencial na produção de bioetanol por ser capaz de assimilar pentoses presentes em biomassa celulósica (SHIN et al, 2015).…”
Section: Figura 3 Perfis De Assimilação De Carboidratos Das Levedurasunclassified